Efficacy and safety of liposomal amphotericin B for deep mycosis in patients with connective tissue disease - Kotani, Takuya; Takeuchi, Tohru; Makino, Shigeki; Hata, Kenichiro; Yoshida, Shuzo; Nagai, Koji; Wakura, Daisuke; Isoda, Kentaro; Hanafusa, Toshiaki (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2013)
The efficacy and safety of liposomal amphotericin B (L-AMB) in the treatment of invasive fungal infections (IFIs) were retrospectively evaluated for patients with connective tissue diseases (CTDs) during treatment with immunosuppressive therapy. Subjects were 13 patients with CTDs complicated by IFI, on the basis of clinical symptoms, imaging findings, and microbiological and histological examinations. All patients were treated with L-AMB. Efficacy and safety were evaluated before and after administration of L-AMB. Underlying diseases were systemic lupus erythematosus for 4 patients, rheumatoid arthritis for 3, microscopic polyangiitis for 2, adult-onset Still disease for 1, dermatomyositis for 1, and mixed connective tissue disease for 1. Eight patients were resistant to other antifungal drugs. Prednisolone was given to 11 patients and the median dose was 10 mg/day. Immunosuppressants were used for 8 patients. The median duration of administration of L-AMB was 8.5 days (range 4–38 days). In proven and probable diagnosis patients (n=5), the treatment was effective for 3 patients and ineffective for 2 (efficacy rate 60 %). Serum 1,3-β-d-glucan antigenemia (BG) levels decreased after treatment in the 2 patients who were positive for BG. Serum Aspergillus galactomannan antigen levels decreased in 3 of 4 patients with Aspergillus infection. No patient died of IFI. Regarding potential adverse reactions, there were no significant changes in serum creatinine and potassium levels. L-AMB is effective and well-tolerated for treatment of IFI in patients with CTDs.